Remote Usability Testing in Portal Web Perpustakaan Nasional Republik Indonesia. - Zuntriana, Ari (Record and Library Journal, 2015)
Portal Web Perpustakaan Nasional Republik Indonesia(PNRI) or Indonesian National Library Web Portal is one of the best resources that support education in Indonesia. With the large collection of librarians, PNRI can reach millions of librarian with various education background and area. To ensure its sustainability, we need to conduct research to know how good is the usability this web portal to the remote user. One of the way is using web usability testing. By using this test, PNRI will get the information about what is needed to be fixed and for the next step it can be used as recommendation in redesigning of the portal. PNRI web portal test will be held using remote usability test method. The research is conducted by combining inquiry with formal usability test, like giving a task to the participant. The sampling method used is random sampling by using 32 participant. Data gathering technique used is using online questionnaire.Â  The research result shows that: (1) most of the participant get difficulties in finding information about service schedule; (2) most of the participant dissatisfied in interface design and arrangement in the homepage of PNRI portal. This research is intended as the starting research. It needs the next research to deepen and complete the information and research findings, especially about portal efficiency.Â